2020
DOI: 10.1186/s40621-019-0228-5
|View full text |Cite
|
Sign up to set email alerts
|

Incidence reporting via online high school concussion surveillance by certified athletic trainers and school nurses, 2015–2018

Abstract: Background: There is an increasing concern over adolescent concussions in sports due to risks of long-term negative effects. This study analyzed data over three school years on reported concussion incidence rates by season, high school grade levels and gender, and reported symptoms by school nurses versus athletic trainers, from New Jersey student-athlete concussion data available from an online school-based surveillance system. Methods: School nurses and athletic trainers reported 300 concussions within five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Our study, in line with others (Meehan 3rd and Mannix 2010 ; McCrory et al 2017 ; Haarbauer-Krupa et al 2018 ; Gonzalez et al 2020 ; Kerr et al 2020 ), revealed higher proportions of health care utilization for SRCs among older aged males as compared to females or younger age groups. We speculate that this finding may be due in part to the prevalence of concussion in male dominated sports such as American football (McCrory et al 2017 ; Gonzalez et al 2020 ; Kerr et al 2020 ). Consistent with prior studies (Meehan 3rd and Mannix 2010 ; Haarbauer-Krupa et al 2018 ), we found higher proportions of health care utilization for NSRCs in younger age groups than older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…Our study, in line with others (Meehan 3rd and Mannix 2010 ; McCrory et al 2017 ; Haarbauer-Krupa et al 2018 ; Gonzalez et al 2020 ; Kerr et al 2020 ), revealed higher proportions of health care utilization for SRCs among older aged males as compared to females or younger age groups. We speculate that this finding may be due in part to the prevalence of concussion in male dominated sports such as American football (McCrory et al 2017 ; Gonzalez et al 2020 ; Kerr et al 2020 ). Consistent with prior studies (Meehan 3rd and Mannix 2010 ; Haarbauer-Krupa et al 2018 ), we found higher proportions of health care utilization for NSRCs in younger age groups than older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…In the context of concussion, the role of educational enjoyment is likely more significant, as most learners experience education due to mandate, either as a result of league rules or state laws. 21 , 22 …”
Section: Introductionmentioning
confidence: 99%
“…Previous research, regardless of subjects’ gender and age, has emphasized the high number of injuries in recreational and collegiate track and field [ 1 – 5 ], as well as elite track and field [ 6 8 ], with a consensus that the main cause of injury is overuse. At least 90% of all overuse injuries (OI) occur at the lower extremities, with a majority of OI occurring at the foot and thigh [ 1 , 7 – 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…There is, however, limited information on how OI develop in elite track and field. Athlete’s previous injury history, high training volume, and different biomechanical factors are assumed to be contributing risk factors [ 6 , 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation